Life of the elderly in Asilo de Molo - Homena, Hiyas Kristine (University of the Philippines in the Visayas, 2007)
This is a study which sought to determine the following: (1) the needs of the elderley in Asilo de Molo, (2) the activities, social and community life in Asilo de Molo, (3) the aspiration and attitudes of the elderlyin Asilo de Molo, (4) the relationship of the elderly in Asilo de molo with their families, and (5) the perception of t5he elderly regarding their health and physical well-being. There are 8 elderly in Asilo de Molo who participated in the research study. The findings showed that the needs of the elderly in the situation were provided how2 ever, some of the clients were not satisfied with the food that was served and lack of medicine. As for their activities, it is found out that most of them were engaged in less strenuous activity such as sleeping. Their life in the institution mainly revolved around the church. Also, the respondents reported that they aspire for good health and longer life since these are the remaining years of their life. They showed positive attitude when asked about the concept of death. Being close to God they believed that death is not be feared instead it should be accepted wholeheartedly and most of them death also means rest. Elderly are closest to those who are inside the institution such as the staff and their fellow resident for the most of them don?t have families left. All of the respondents admitted that they have weak body condition and are prone to sickness such as arthritis and fever. Most reported that they have difficulty in seeing, hearing, remembering, and chewing.